The path to smart farming: Profiling farmers' adoption of technologies in Türkiye - Huseyin Tayyar Guldal; Hasan Sanli; Metin Turker (Agricultural Economics (AGRICECON))
This study investigates the characteristics associated with the adoption of smart farming technologies in Turkish agriculture. By surveying 325 farmers across six regions in Türkiye, the research identifies key attributes influencing adoption patterns. Four distinct profiles emerge: technology users, non-users, young educated female farmers, and traditionalists. Exploratory findings from Multiple Correspondence Analysis (MCA) indicate that attributes such as agricultural insurance, credit utilisation, knowledge of smart farming systems, and tractor ownership are commonly observed among technology users. Ordinal logistic regression further quantifies these associations, highlighting the significant role of financial accessibility and knowledge dissemination in shaping adoption likelihoods. Non-users, on the other hand, are characterised by smaller landholdings, lack of credit use, limited awareness, and absence of tractor ownership, reflecting structural barriers to adoption. Tailored financial solutions and shared machinery parks could help address these challenges. Empowering young, educated women farmers, identified as a key demographic for innovation, offers an opportunity to catalyse broader technology adoption. By addressing knowledge gaps and fostering inclusive policies, this study provides actionable insights to accelerate the technological transformation and sustainability of Türkiye's agricultural sector.